Physical culture for Americans - Swingle, Miriam Esther (My University, 1896)
Introduction: As man advances, his mind growing stronger, the limit of his mental powers widen, he recognizes that there will come a time when comparatively little can be done unless his body is developed proportionally as is his mind. His nature is such that mind and body are … and as in the order of Nature, body comes first in importance so it should be just in importance of correct development.
Citation: Swingle, Miriam Esther. Physical culture for Americans. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Man; Mental powers; Nature; Mind and Body; Theses; Manuscripts (documents)